Long-term Outcomes of Modified 360-Degree Suture Trabeculotomy for Uveitic Glaucoma Compared With Primary Open Angle Glaucoma. Issue 8 (2nd August 2022) - Kijima, Riki; Shinmei, Yasuhiro; Chin, Shinki; Kanaya, Rina; Shinkai, Akihiro; Ohguchi, Takeshi; Namba, Kenichi; Ishida, Susumu
Abstract : Précis: A Kaplan-Meier survival curve analysis showed no significant differences in success rates between uveitic glaucoma (UG) and primary open angle glaucoma (POAG) 120 months after modified 360-degree suture trabeculotomy, which was effective for both groups in the long term. Purpose: The aim of this study was to examine the outcomes of modified 360-degree suture trabeculotomy in patients with UG as compared with those with POAG. Patients and Methods: This was a retrospective, nonrandomized, and comparative case series study. Modified 360-degree trabeculotomy using a 5-0 nylon suture (S-LOT) was performed on 51 eyes of 51 patients (54.4±13.4 y) with UG between October 2005 and January 2012 at Hokkaido University Hospital. Age-matched patients with POAG who underwent S-LOT during the same period were enrolled as controls. Written informed consent was obtained from all patients enrolled in the present study. Surgical success was defined as an intraocular pressure (IOP) <18 mm Hg with similar or lower doses of antiglaucoma medications. Kaplan-Meier survival curves of surgical failure were analyzed and compared between UG and POAG. Results: The mean follow-up periods (±SD) for UG and POAG were 104.8±44.0 and 98.1±36.3 months ( P =0.23), respectively. Mean preoperative IOP in UG and POAG were 34.9±11.0 and 25.3±9.4 mm Hg ( P <0.001), respectively. After surgery, mean IOP in UG and POAG decreased to 12.0±4.1 and 13.8±3.2 mm Hg, respectively, at 60 months, and 12.1±5.6 and 12.4±1.8 mm Hg ( P =0.86), respectively, at 120 months. The Kaplan-Meier survival curve analysis showed no significant differences in success rates between UG and POAG at the end of the follow-up (Log-rank test, P =0.13). Success rates in UG and POAG were 70.0 and 62.5% at 60 months, and 67.5 and 41.2% at 120 months, respectively. Conclusion: These results suggest that S-LOT is effective for UG and POAG alike.